Implementation of lean practices in water heater manufacturing industry. (2021) - Barot, R.S.; Raval, Keyur; Beravala, Hardik; Patel, Amar
Abstract: Increased competition in market has forced small and medium scale industries to re-examine ways of manufacturing. For many years large scale industries have implemented lean to sustain in the business. Small and medium scale productions avoided to use lean tools due to monetary factors. The fruitfulness of lean execution in large scale sector now realized benefits focusing extreme need in small scale industries also. In this work it is aimed to present a framework of lean implementation using primary lean tools. Future state Value Stream Map and proposed String Diagram are developed and implemented indicating the improvement proposal and possible time reductions as a result of modification. Efforts are made in eliminate wastes in production flow line using various lean tools. As a result it reduced waiting time from 645 min to 462 min, productivity increased from 50% to 70% and material movement reduced from 283.08 m to 153.92 m.